Ploidy level determination in genetically modified polyploid striped catfish Pangasianodon hypophthalmus Sauvage, 1878 based on the number of nucleoli per cell - Muhammad Sami Daryanto; Odang Carman; Dinar Tri Soelistyowati Soelistyowati; Rahman Rahman (Jurnal Iktiologi Indonesia, 2019)
The variation in the maximum number of nucleoli per cell in diploid and tetraploid striped catfish Pangasianodon hypophthalmus Sauvage, 1878 in attempts to verify the validity of nucleoli counting as an indirect method for polyploidy identification in fish. The aims of this research is to determine ploidy level of striped catfish based on maximum number of nucleoli per cell. Diploid striped catfish was produced by fertilizing eggs without thermal-shock and tetraploid fish was obtained by fertilizing eggs and applying thermal-shock induction with 4oC for 25 minutes at zygotic age 28 minutes after fertilization prior to first cleavage stage of zygote. The hatching rate of diploid group and tetraploid group were 81,35±0,73% and 3,39±1,78% and survival rate during 15 days rearing were 88,67±5,25% and 83,33±5,73%, respectively. The frequency of one, two, three, and four nucleoli per cell were counted based on each sample observation of 450-550 cells. Cells of diploid individuals had one, and maximum two nucleoli per cell, while tetraploid there were one, two, three, and maximum four nucleoli per cell. Anomaly in the silver-stained appearance at the maximum number of three nucleoli per cell indicated tetraploid individuals as verified by chromosome counting method. Ploidy level determination of striped catfish using the number of nucleoli per cell has a potential for rapid identification. Abstrak Penentuan variasi jumlah maksimum nukleolus per sel pada individu diploid dan tetraploid patin siam Pangasianodon hypophthalmus Sauvage, 1878 dilakukan dalam upaya verifikasi ketepatan penghitungan nukleolus sebagai metode tidak langsung dalam identifikasi ikan poliploid. Penelitian ini bertujuan menentukan tingkat ploidi ikan patin siam berdasarkan jumlah maksimum nukleolus per sel. Diploid patin siam dihasilkan melalui fertilisasi buatan antara telur dan sperma tanpa kejutan suhu sedangkan tetraploid patin siam dihasilkan melalui fertilisasi antara telur dan sperma serta di induksi menggunakan kejutan suhu 4oC dengan durasi kejutan 25 menit pada umur zigot 28 menit setelah fertilisasi sesaat sebelum mitosis I. Persentase penetasan kelompok perlakuan diploid 81,35±0,73% dan kelompok perlakuan tetraploid 3,39±1,78%. Sintasan kelompok perlakuan diploid 88,67±5,25% dan kelompok tetraploid 83,33±5,73% selama 15 hari pemeliharaan. Frekuensi satu, dua, tiga dan empat nukleoli per sel dihitung berdasarkan pengamatan 450-550 sel setiap individu yang diamati. Sel individu diploid memiliki satu dan maksimum dua nukleoli per sel, sedangkan individu tetraploid memiliki satu, dua, tiga, dan maksimum empat nukleoli per sel. Anomali muncul melalui pewarnaan perak nitrat pada jumlah maksimum tiga nukleoli per sel menunjukkan individu tersebut tetraploid yang diverifikasi menggunakan metode penghitungan kromosom. Penentuan ploidi pada ikan patin siam menggunakan penghitungan jumlah nukleolus per sel memiliki potensi dalam identifikasi secara cepat.